Determining the level of high-speed abilities of young soccer players aged from 10 to 12 years - Lebedev S.I (Kharkov National Pedagogical University, 2013)
The problems of high-speed training of young players were considered. Carried out an analytical review of the scientific literature on the specific sources of development and control the speed of the players. The changes of speed training of young players 10-12 years during 2010-2012. The study involved 42 different football game role (forwards, midfielders, defenders) children's football academy "Metalist". Join the results of testing carried out by a system of training SMARTSPEED. On the field, it was found 4 lines wireless gates that automatically tablet computer controlled times taken to run the distance. It was found that with the increase in training time performance speed was significantly different compared to the previous year by 15 m intervals running from the scene, 30 yards from the scene, and 30 m on the move. Recommended directions for planning the preparation of young players for the development of high-speed qualities.